Open theism on providence and theodicy : an Arminianized evangelicalism - Olsen, Peter Flemming ([Copenhagen?] : : Teologiske Fakultat, 2009)
"In this book, Graham Oppy examines contemporary arguments for and against the existence of God. He shows that none of these arguments is powerful enough to change the minds of reasonable participants in debates on the question of the existence of God. His conclusion is supported by detailed analyses of the contemporary arguments, as well as by the development of a theory about the purpose of arguments, and the criteria that should be used in judging whether or not arguments are successful. Oppy discusses the work of a wide array of philosophers, including Anselm, Aquinas, Descartes, Locke, Leibniz, Kant, Hume, and, more recently, Plantinga, Dembski, White, Dawkins, Bergman, Gale, and Pruss."--BOOK JACKET.
Includes bibliographical references (p. 375-396)
Keywords: Open theism--History of doctrines--20th century; Evangelicalism; Arminianism; God--History of doctrines--20th century; Providence and government of God--History of doctrines--20th century